Persepsi Dan Penghargaan Masyarakat Atas Doktrin Pemisahan Ruang Publik Dan Domestik Berbasis Gender Di Yogyakarta - Astuti, Dwi (Universitas Islam Majapahit, Indonesia, 2022)
The division of roles in society has historically remained faithful to gender, namely male and female.Although the basis of this division still stands, it always causes debate from time to time. DebateThese appear related to the expressions